CRITERIA FOR MODERNIZATION AND EVALUATION OF THE CONTENT OF THE TRAINING PROCESS OF OFFICERS ON THE BASIS OF A COMPETENCY-BASED APPROACH - Khalilayev Batirjon Taxirovich (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the role of professional competence in the training of future officers in higher military education, the criteria for modernization and evaluation.